Modification of low-molecular-weight polyethylene through grafted copolymerization with methyl acrylate - Valentin Kudyshkin; Nurad Bozorov; Ruslan Madiev; Bektemir Ruziev; Nurbek Ashurov; Sayera Rashidova (Polyolefins Journal, 2025)
Copolymers of methyl acrylate were grafted onto low-molecular-weight polyethylene in the presence of benzoyl peroxide in o-xylene. The formation of these copolymers was confirmed by functional analysis of the ether groups and Fourier-transform infrared spectroscopy. Various synthesis patterns were demonstrated, which furnished grafted copolymers with a wide range of compositions. X-ray diffraction analysis showed that grafting led to changes in the crystalline structure of low-molecular-weight polyethylene. The grafting sequences of the methyl acrylate units may disrupt the order of the crystalline planes in polyethylene, and with an increase in their content, the crystalline phase in polyethylene becomes less prominent. These copolymers can be used as compatibilizers for CB-filled polyethylene (CB: carbon black). The effect of the grafted copolymers on the properties of high-density polyethylene composites containing CB was evaluated. The composites of polyethylene and the grafted copolymers exhibited enhanced thermal stability, plausibly associated with a decrease in the average size of the CB particles.